2002
DOI: 10.1152/ajpregu.00019.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical phenotype of hypothalamic neurons showing Fos expression 23 h after intracranial AgRP

Abstract: in a population of neurons in the arcuate nucleus (ARC) of the hypothalamus and stimulates food intake for up to 7 days if injected intracerebroventricularly. The prolonged food intake stimulation does not seem to depend on continued competition at the melanocortin-4 receptor (MC4R), because the relatively specific MC4R agonist MTII regains its ability to suppress food intake 24 h after AgRP injection. Intracerebroventricular AgRP also stimulates c-Fos expression 24 h after injection in several brain areas, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 71 publications
1
38
1
1
Order By: Relevance
“…The observation that the pattern of fos expression differs between the acute and longer-term responses to intracerebroventricular AgRP was proposed as evidence that the short-term and long-term responses to AgRP have different mechanisms (22). It could also be evidence of the activation of neural circuits to counteract the long-term effects of AgRP as suggested by Berthoud and colleagues (57). The underlying mechanism(s) responsible for the prolonged responses to changes in melanocortin receptor modulation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the pattern of fos expression differs between the acute and longer-term responses to intracerebroventricular AgRP was proposed as evidence that the short-term and long-term responses to AgRP have different mechanisms (22). It could also be evidence of the activation of neural circuits to counteract the long-term effects of AgRP as suggested by Berthoud and colleagues (57). The underlying mechanism(s) responsible for the prolonged responses to changes in melanocortin receptor modulation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although NPY mRNA levels are reduced 6 h after refeeding, AgRP levels remain elevated (Swart et al 2002). This prolonged response results in a greater cumulative effect on food intake than NPY, and probably involves more diverse signalling pathways than the melanocortin pathway alone (Hagan et al 2000, Zheng et al 2002.…”
Section: Hypothalamic Neuropeptidesmentioning
confidence: 99%
“…AgRP acts as an antagonist at melanocortin-4 receptors and causes profound and prolonged hyperphagia; under some conditions the hyperphagia may be apparent for as long as 7 days after intracerebroventricular administration (15,38,50). Pharmacological characterization of the human agouti signaling peptide showed that, as expected, it behaves as a competitive antagonist of ␣-MSH and melanocortin receptors (48).…”
mentioning
confidence: 82%
“…The latter nucleus tends to be a site where feedinginhibitory inputs are processed (45,50). Thus urocortin and CRH injected into the paraventricular nucleus reduced feeding induced by food deprivation or by NPY (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation